Influence of Different Proportions of External Irrigation During the Er,Cr:YSGG Laser Irradiation on Wear and Roughness of Root Surface - de Oliveir, Guilherme José Pimentel Lopes; Pinotti, Felipe Eduardo; da Luz Carvalho, Heglécia; Scardueli, Cássio Rocha; Marcantonio, Rosemary Adriana Chiérici (Journal of Lasers in Medical Sciences, 2016)
Introduction: The aim of this study was to evaluate the influence of different levels of external irrigation during irradiation with an erbium, chromium: yttrium-scandium-gallium-garnet (Er,Cr:YSGG) laser on the roughness and wear of dental tissue during scaling procedures. Methods: Twenty-Five uniradicular bovine teeth had the proximal surfaces planed and divided into 3 regions: upper, middle and lower. The upper region was treated with hand instruments, the middle region was not treated and served as a control, and the lower region was treated by the Er,Cr:YSGG laser. The teeth were randomly divided into five groups according to the different proportions of external irrigation used during the laser irradiation: G1: 10%; G2: 20%; G3: 30%; G4: 40% and G5: 50%. The samples were analyzed for roughness and wear on the root surface irradiated with the laser. Results: There were no differences in the surface roughness and wear parameters between the groups irradiated with the laser, but the laser irradiation produced a rougher surface of the dentin than treatment with hand scaling. Conclusion: Changes in the external irrigation level did not influence the wear and roughness of root surfaces treated with an Er,Cr:YSGG laser